Konvencija didaskalij - Zajc, Ivana (Jezik in slovstvo, 2017)
In the introductory paragraph, the article distinguishes the theoretical orientations in research of stage directions and presents the findings of previous research of their historical evolution, comparing different typologies of stage directions. It points out that the definitions often do not take into account the historical changes of stage directions, and fail to reflect their own theoretical standpoint. The article presents a definition of stage directions that takes into account the dichotomy of their various properties. It sums up the theoretical findings about contemporary subversions of the convention of stage directions, analysing them in Katarina Marinčič's novel Po njihovih besedah. The article parses the link between stage directions and the intertextuality of the novel.
Keywords: Marinčič, Katarina, 1968-; "Po njihovih besedah"; Slovene literature; slovenska književnost; slovenski romani; metabesedilnost; didaskalije; tipologije didaskalij; intertekstualnost; Intertextuality